2006
DOI: 10.1016/j.jpainsymman.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin Levels in the Cerebrospinal Fluid of Chronic Pain Patients With or Without Intrathecal Administration of Morphine

Abstract: The neuropeptide nociceptin/orphanin FQ (N/OFQ) is the endogenous ligand for the opioid-like receptor ORL-1 and is thought to be involved in pain transmission and modulation. Human studies have not yet defined its role in pain patients. The aims of this study were 1) to verify the presence of N/OFQ in the cerebrospinal fluid (CSF) of human controls and patients with chronic noncancer pain, including those treated with intrathecally administered morphine, and 2) to determine whether pain or treatment with long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…Furthermore, SR16835, which is inactive in blocking tail flick acute pain, was able to attenuate SNL-induced mechanical allodynia, an action also blocked by SB-612111 (Khroyan et al, 2011). These results are consistent with chronic pain-, as well as chronic inflammation-induced changes in the levels of NOP receptor mRNA, N/OFQ peptide levels, and ppN/OFQ mRNA levels in rodents (Andoh et al, 1997;Itoh et al, 2001;Briscini et al, 2002;Witta et al, 2003) and humans (Raffaeli et al, 2006) and once again suggest that NOP agonists might have better success in treatment of chronic or inflammatory rather than nociceptive acute pain.…”
Section: B Bifunctional Compoundssupporting
confidence: 77%
“…Furthermore, SR16835, which is inactive in blocking tail flick acute pain, was able to attenuate SNL-induced mechanical allodynia, an action also blocked by SB-612111 (Khroyan et al, 2011). These results are consistent with chronic pain-, as well as chronic inflammation-induced changes in the levels of NOP receptor mRNA, N/OFQ peptide levels, and ppN/OFQ mRNA levels in rodents (Andoh et al, 1997;Itoh et al, 2001;Briscini et al, 2002;Witta et al, 2003) and humans (Raffaeli et al, 2006) and once again suggest that NOP agonists might have better success in treatment of chronic or inflammatory rather than nociceptive acute pain.…”
Section: B Bifunctional Compoundssupporting
confidence: 77%
“…A significant increase in brain N/OFQ immunoreactivity has also been demonstrated in SNL rats (Sun et al, 2001), as well as an increase in NOP receptors in superficial laminae of the rat spinal cord subsequent to CFA injection, as determined by in vitro autoradiography (Jia et al, 1998). Furthermore, increased levels of N/OFQ have been reported in the cerebrospinal fluid of patients with chronic pain (Raffaeli et al, 2006). These studies suggest that exogenously applied NOP agonists and/or antagonists may have activity in chronic pain animals.…”
Section: Nop Agonists In Acute Versus Chronic Pain 691mentioning
confidence: 77%
“…Indeed, a recent clinical study found higher levels of N/OFQ in the CSF of chronic pain patients compared to controls. In that study, N/OFQ levels were reduced over 75% in chronic pain patients (mainly males) who received prolonged intrathecal morphine compared to male and female patients receiving no morphine (Raffaeli et al, 2006). …”
Section: Discussionmentioning
confidence: 85%